PENGENALAN TEKNOLOGI EKSTRAKSI ZAT WARNA ALAM UNTUK PEWARNA ALAMI BATIK DI UKM BATIK TULIS “KEBON INDAH”, BAYAT, KLATEN - Achmad Chafidz; Ajeng Yulianti Dwi Lestari (Jurnal Komunitas : Jurnal Pengabdian kepada Masyarakat, 2021)
Batik Tulis is one of traditional Indonesian culture that must be preserved. UKM Batik Tulis “Kebon Indah” is one of Batik Tulis or Cap industries that uses natural dyes for coloring the Batik. This UKM is located in Desa Kebon, Bayat, Klaten. As a traditional UKM, of course there are many problems that must be solved. This community service activity aims to identify the existing problems and provide solutions or ideas to further develop UKM Batik Tulis “Kebon Indah” especiallly in terms of the production process of Batik Tulis. Additionally, also to introduce natural dye extraction process technology for better coloring results the Batik Tulis. This service community was carried out by interview, direct observation, and presentation/counseling methods. From this community service activity, the members of UKM Batik Tulis “Kebon Indah” have obtained new knowledge about the natural dye extraction process technology. Additionally, several recommendations to solve the current problems have been conveyed to the UKM, such as: pretreatment of raw natural coloring sources and application of natural dye extraction process technology on the production process of the Batik Tulis.